2014
DOI: 10.1007/s10578-014-0515-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Internalizing and Externalizing Comorbidities and Functional Outcomes for Children with ADHD

Abstract: This study examined functional outcomes for children with ADHD by comorbidity status. Children with ADHD (5-13 years) were recruited from 21 pediatric practices and followed up 12 months later (n = 199). Parent and teacher-reported baseline and 12 month surveys measured peer problems, daily functioning, quality of life (QoL), parent mental health, and family QoL. The Anxiety Disorders Interview Schedule for Children IV assessed mental health comorbidities at baseline. Linear regression models were conducted, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Children with ADHD and both internalizing and externalizing co‐morbidities seemed to be at particular risk of health‐related impairments in this study. This is consistent with recent research reporting that children with co‐occurring co‐morbidities, in addition to ADHD, have poorer daily functioning compared with children with ADHD alone (Armstrong et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Children with ADHD and both internalizing and externalizing co‐morbidities seemed to be at particular risk of health‐related impairments in this study. This is consistent with recent research reporting that children with co‐occurring co‐morbidities, in addition to ADHD, have poorer daily functioning compared with children with ADHD alone (Armstrong et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies in psychiatric conditions have largely focused on schizophrenia [3540]. There has been limited research on other psychiatric illnesses [41,42]. Specifically, caregivers of youth presenting with myriad diagnoses, such as ADHD [43], Tourette syndrome [44], and neurodevelopmental disorders [45] often experience higher parenting stress relative to caregivers of typically developing children, though stress did not always correlate directly with levels of symptom severity; some comorbid psychopathology (including OCD; [44]) was postulated to be contributing more to the increased parenting stress.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, previous research has found relationships between both child/adolescent problems and family/contextual variables. For example, Armstrong et al (2015) have shown longitudinal associations between baseline internalizing and externalizing problems and poor family quality of life at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, according to the work of Armstrong et al (2015) we explored a serial multiple mediator model between child/adolescent’s ADHD and parenting stress that included a direct path from children’s conduct and emotional problems to family and contextual factors. We hypothesized that one of the mechanisms by which ADHD is linked to mothers’ stress is through the effects of the emotional and behavioral difficulties experienced by children with ADHD on context and family functioning.…”
Section: Introductionmentioning
confidence: 99%